Keterkaitan kemiskinan, kecukupan energi dan protein dengan kejadian stunting balita di Puskesmas 11 Ilir Palembang - Nathasa Weisdania Sihite; Muhammad Syafwan Chaidir (University of Darussalam Gontor, 2022)
Background: Stunting is nutritional problem that influence the growth of toddlers to be not suitable for their age. Main problem of stunting divided into several factor among other is the level of nutritional adequacy from macro and micronutrients, such as social and economic factors that influence it. Objective: This study aims to determine and analyze the relationship between poverty and nutritional adequacy (energy and protein) of children under five with the incidence of stunting at Puskesmas 11 Ilir Palembang. Methods: This study used a cross-sectional design, sample of 33 children aged 2-5 years. The sample was selected by purposive sampling using the Lemeshow formula. Measurement of nutritional adequacy using 2x24 hour recall. Data processing was carried out using Excel, WHO-Anthro, and SPSS with Chi-Square test. Results: The energy adequacy level of stunting toddlers is mostly in the moderate deficit category (51.5%), there is a significant relationship between energy adequacy level and incidence of stunting. Protein adequacy level of stunting in the good category with 72.7% from total sample. The analysis of the poverty level of the families of children under five was found that the majority were below the poverty line with a percentage of 78.8% of the total sample. The research found that poverty is directly related to the incidence of stunting (p = 0.023). Conclusion: The status of poverty and the level of nutritional adequacy of both Energy and Protein in infants can be used as an indicator in analyzing the problem of stunting in children underfive.Keywords : Energy, nutritional adequacy, poverty, protein, stunting AbstrakLatar Belakang: Stunting merupakan masalah gizi kronis yang menyebabkan pertumbuhan balita menjadi tidak optimal. Masalah utama dalam stunting dapat dilihat dari berbagai faktor salah satunya adalah tingkat kecukupan gizi dan indikator kemiskinan. Tujuan: Penelitian ini bertujuan untuk mengetahui dan menganalisis hubungan kemiskinan dan kecukupan gizi (energi dan protein) balita dengan kejadian stunting yang terjadi pada balita di Puskesmas 11 Ilir Palembang. Metode: Penelitian ini menggunakan desain cross- sectional study, sampel yang diambil berjumlah 33 orang berusia 2-5 tahun. Sampel dipilih dengan cara purposive sampling dengan menggunakan rumus Lemeshow. Pengukuran kecukupan gizi balita menggunakan recall 2x24 jam. Pengolahan data dilakukan menggunakan Exel,WHO-AnthroPlus dan SPSS. Analisis data dilakukan dengan uji Chi-Square. Hasil: Tingkat kecukupan energi balita stunting sebagian besar berada dalam kategori defisit sedang (51,5%), terdapat hubungan signifikan antara tingkat kecukupan energi pada balita dengan kejadian stunting. Tingkat kecukupan protein balita berada dalam kategori baik (72,7%) dari total sampel. Hasil analisa tingkat kemiskinan keluarga menjelaskan bahwa mayoritas berada di bawah garis kemiskinan (78,8%). Pada penelitian ini didapatkan hasil bahwa kemiskinan berhubungan langsung dengan kejadian stunting (p=0,023). Kesimpulan: Status kemiskinan dan tingkat kecukupan gizi baik Energi dan Protein pada balita dapat dijadikan indikator dalam menganalisis masalah stunting pada balita.